Signal design for underwater acoustic positioning systems based on orthogonal waveforms. (1st May 2016) - Han, Yunfeng; Zheng, Cuie; Sun, Dajun
Abstract: Autonomous underwater vehicles (AUVs) or remotely operated vehicles (ROVs) are commonly used in deep water industries. Because the sound wave is the most effective carrier for transmitting information underwater, underwater acoustic positioning systems (UAPSs) are regarded as essential positioning and navigation components of AUVs or ROVs. Multi-target positioning is the most important emergent trend being explored for current UAPSs, within which signal design is a major issue. The designed waveforms determine the detection performance, user number, and system complexity of the UAPS. Conventional UAPSs use chirp signals or FM signals, which are disadvantaged by low user number, complex implementation, and low utilization bandwidth. In effort to solve these problems, we designed a group of signals based on orthogonal waveforms, then used a genetic algorithm to design a group of phase-coding signals, and finally analyzed the system as established in terms of time measurement precision, performance in the multipath environment, and the aliasing effects of multi-target signals. Simulation results showed that the signals we designed have ideal correlation performance and high time resolution. We further conducted an experiment in shallow water to test the proposed method׳s performance, and again found that the signals are suitable for multi-target UAPSs and thus show favorable potential in ocean engineering applications. Abstract : Graphical abstract: